2012
DOI: 10.1186/1471-2407-12-233
|View full text |Cite
|
Sign up to set email alerts
|

Effect of inhibition of the Ubiquitin-Proteasome System and Hsp90 on growth and survival of Rhabdomyosarcoma cells in vitro

Abstract: BackgroundThe ubiquitin-proteasome system (UPS) and the heat shock response (HSR) are two critical regulators of cell homeostasis, as their inhibition affects growth and survival of normal cells, as well as stress response and invasiveness of cancer cells. We evaluated the effects of the proteasome inhibitor Bortezomib and of 17-DMAG, a competitive inhibitor of Hsp90, in rhabdomyosarcoma (RMS) cells, and analyzed the efficacy of single-agent exposures with combination treatments.MethodsTo assess cytotoxicity i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 58 publications
2
13
0
Order By: Relevance
“…This conclusion is supported by the findings showing increased levels of the mRNAs and proteins linked to autophagosome elongation, and LC3BII conjugation to the autophagosomal membrane as well as by electron microscopy. The pro-survival activity of the autophagy pathway in select cancers has been established (Clarke et al, 2012;Hambright and Ghosh, 2017;Jiang and Mizushima, 2014;Levine and Kroemer, 2008;Maycotte and Thorburn, 2014), and, consistent with our results, rhabdomyosarcomas also coopt this pro-survival pathway (Peron et al, 2012;Rapino et al, 2014). Surprisingly, inhibition of autophagy, but not ERAD, re-sensitized RMS13-R cells to MAL3-101.…”
Section: Rms13-r and Rms13 Cells (supporting
confidence: 90%
“…This conclusion is supported by the findings showing increased levels of the mRNAs and proteins linked to autophagosome elongation, and LC3BII conjugation to the autophagosomal membrane as well as by electron microscopy. The pro-survival activity of the autophagy pathway in select cancers has been established (Clarke et al, 2012;Hambright and Ghosh, 2017;Jiang and Mizushima, 2014;Levine and Kroemer, 2008;Maycotte and Thorburn, 2014), and, consistent with our results, rhabdomyosarcomas also coopt this pro-survival pathway (Peron et al, 2012;Rapino et al, 2014). Surprisingly, inhibition of autophagy, but not ERAD, re-sensitized RMS13-R cells to MAL3-101.…”
Section: Rms13-r and Rms13 Cells (supporting
confidence: 90%
“…This pilot study has expanded our understanding of the cross-talk between apoptosis and autophagy controlling TMZ-induced apoptosis. It has been shown that the maintenance of cellular viability in RH30 cells is dependent on baseline autophagy 25 , while loss of ATG7 or Baf-A1 treatment can negatively regulate proliferation of RH30 cells 26 , 27 . We found that Baf-A1 inhibited baseline autophagy in RH30 and C2C12 cells and decreased their viability.…”
Section: Discussionmentioning
confidence: 99%
“…In RH30 cells, autophagy is known to be a crucial process in the maintenance of cellular viability and proliferation 25 . Furthermore, inhibition of autophagy by the Atg7 knockdown, or pharmacological inhibition with chloroquine or Baf-A1 treatment, has been demonstrated to decrease cell growth and reduced viability in RMS cell lines 26 , 27 .…”
Section: Introductionmentioning
confidence: 99%
“…The proteasome inhibitor, bortezomib, functions through inhibition of the 26S proteasome, leading to apoptosis, cell cycle arrest, and deregulated NF-KB signaling and is currently approved for use in hematologic malignancies [ 17 20 ]. In vitro studies have shown RMS cell lines to exhibit increased rates of apoptosis and cell cycle arrest when treated with bortezomib both as a single agent as well as in combination [ 19 , 20 ]. AZD1775 is a selective tyrosine kinase inhibitor of the Wee1 kinase which regulates the cell cycle through phosphorylation and inhibition of cyclin-dependent kinase 1.…”
Section: Introductionmentioning
confidence: 99%